Resultat av tjugofem års mätningar av Cs-137-halter i älg i Uppsala län - Weimer, Robert (SLU/Dept. of Soil and Environment, 2011)
At the end of April 1986 reactor number 4 of the nuclear power plant at Chernobyl explod-ed and large amounts of radioactive particles were then released into the atmosphere due to both the explosion as well as the consecutive fire of the graphite core. A cloud of radioac-tivity was spread over the northern hemisphere, including Sweden, due to the prevailing wind directions. The radioactive particles were washed out from the cloud by rain and snowfall in some areas of Sweden and deposited on the ground. The deposited radionu-clides, primarily cesium and iodine isotopes, were later absorbed into the soil and taken up by the roots of the plants. Some of these radionuclides, like 137Cs, still persist in some of the terrestrial ecosystems at relatively high concentrations which lead to contamination of the meat of moose, roe deer and wild boar even today.